ICT Update 91: Next-generation ACP agriculture – innovations that work - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Digital as well as other technical and institutional innovations underpin the success of agriculture in developing countries in Africa, the Caribbean and the Pacific (ACP). Such innovations are encouraging a new generation of young ‘agripreneurs’ to tackle agri-food challenges, explore ways to build resilience to climate change, and improve the incomes and livelihoods of people in agriculture. This issue of ICT Update brings together selected experiences of agricultural practitioners working close to the ‘front line’, bringing innovation and next-generation ideas to agriculture for development projects, and helping them reach, benefit and empower smallholder producers, leading to sustainable change.